Phosphodiesterase Type-5 Inhibitor Prescription Patterns in the United States Among Men with Erectile Dysfunction: An Update. Issue 5 (3rd March 2020) - Mulhall, John P.; Chopra, Ishveen; Patel, Dipen; Hassan, Tarek A.; Tang, Wing Yu
Abstract: Background: While phosphodiesterase type-5 inhibitors (PDE5Is) are highly effective for the treatment of erectile dysfunction (ED) and well tolerated, updated data on prescription patterns have been limited in real-world settings. Aim: To describe men in the United States who are prescribed PDE5Is for ED treatment and to evaluate patterns of initiation, switching, and treatment overlap. Methods: This retrospective claims study used MarketScan Commercial and Medicare Supplement Databases from January 1, 2010, to December 31, 2015, to identify initial PDE5I claims (index date) for sildenafil, tadalafil, and/or vardenafil. Adults aged ≥18 years with ED were identified between July 1, 2010, and December 31, 2014, allowing for a 6-month preindex and 12-month follow-up period from the index date. Outcomes: Outcomes included patient demographics and treatment-related patterns after treatment initiation. Results: A total of 106, 206 identified patients met all inclusion criteria. Of these, 51, 694, 40, 193, and 14, 319 had initial claims for sildenafil, tadalafil, and vardenafil, respectively. Mean age was 50.35 years, and comorbidities included dyslipidemia (44.17%), hypertension (43.09%), diabetes (15.32%), and depression (10.61%). More patients (48.67%) initiated on sildenafil than tadalafil (37.85%) or vardenafil (13.48%). Rate of switching was lower in the 60 days after the end of day supply of the initial prescription in the sildenafil cohort (2.71%) compared with the tadalafil (2.81%) and vardenafil (3.88%) cohorts ( P < .001 for sildenafil vs tadalafil or vardenafil). Treatment overlap was lower in the sildenafil cohort (0.35%) than in the tadalafil (0.75%) and vardenafil (0.62%) groups ( P < .001 for sildenafil vs tadalafil or vardenafil). Clinical Implications: These findings provide insight into updated patterns of PDE5I prescriptions in the United States and may aid in clinical decision-making. Strengths & Limitations: Strengths include the large sample size, long data coverage period, and the real-world nature of the study. Limitations include the retrospective study design, use of data collected with a primary focus of claims, and lack of further details regarding reasons that drive switching. Actual rates of ED and impact on prescription patterns may be underestimated because the claims database only captured patients electing to visit a health-care provider. Conclusion: Among men with ED in the United States, rates of switching and treatment overlap were low for all PDE5Is but were found to be the lowest for sildenafil compared with tadalafil and vardenafil.